2020
DOI: 10.1002/dc.24518
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary human papillomavirus genotyping and correlations to peniscopy, cytology, and histopatology on over 1000 males

Abstract: Objectives: To explore male human papillomavirus (HPV) contemporary genotyping epidemiology and correlations to peniscopy, cytology, and histopatology. Methods: Medical records of patients who had been submitted to HPV infection screening with genotyping, peniscopy, cytology, and histopathology in a period of 2 years were reviewed. Frequency analysis and correlations between the diagnostic tools were established. Results: Genotype of 1132 men resulted in 69.2% (784) positivity for HPV DNA, 78% classified as hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In Brazil, a contemporary representative cohort of 1.132 men screened for HPV showed that over two-thirds are positive for human HPV DNA, 78% of high risk and over half with co-infections. The most frequently identified types were HPV-6, HPV-42, and HPV-16 (37).…”
Section: Commentmentioning
confidence: 99%
“…In Brazil, a contemporary representative cohort of 1.132 men screened for HPV showed that over two-thirds are positive for human HPV DNA, 78% of high risk and over half with co-infections. The most frequently identified types were HPV-6, HPV-42, and HPV-16 (37).…”
Section: Commentmentioning
confidence: 99%